Compounds Isolated from the Ethyl Acetate Fraction of Canna edulis Ker Gawl Rhizomes - Thi Van Anh, Nguyen; Hong Luyen, Le; Thi Minh Hang, Nguyen; Thi Thom, Vu; Thanh Tung, Bui (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 37 No 2, 2021)
Three compounds were isolated from the rhizome part of Canna edulis for the first time including liquiritigenin, methyl caffeate and uracil. Their structures were elucidated by spectroscopic methods as MS and NMR. Keywords Canna edulis Ker Gawl, liquiritigenin, methyl caffeate, uracil. References [1] T. H. Vu, Q. U. Le, Edible Canna (Canna edulis Ker), A Potential Crop for Vietnam Food Industry, International Journal of Botany Studies, Vol. 4, No. 4, 2019, pp. 58–59. [2] N. Tanakar, The Utilization of Edible Canna Plants in Southeastern Asia and Southern China, Economic Botany, Vol. 58, No. 1, 2004, 112–114. [3] A. S. A. Snafi, Bioactive Components and Pharmacological Effects of Canna indica - an Overview, International Journal of Pharmacology and Toxicology, Vol. 5, No. 2, 2015, pp. 71–75. [4] X. J. Zhang, Z. W. Wang, Q. Mi, Phenolic Compounds from Canna edulis Ker Residue and Their Antioxidant Activity, LWT - Food Science Technology, Vol. 44, No. 10, 2011, pp. 2091–2096, https://doi.org/10.1016/j.lwt.2011.05.021. [5] F. Xie, S. Gong, W. Zhang, J. Wu, Z. Wang, Potential of Lignin from Canna edulis Ker Residue in The Inhibition of α-d-glucosidase: Kinetics and Interaction Mechanism Merging with Docking Simulation, International Journal of Biology and Macromolecules, Vol. 95, 2017, pp. 592–602, https://doi.org/10.1016/j.ijbiomac.2016.11.100. [6] J. Zhang, Z. W. Wang, Soluble Dietary Fiber from Canna edulis Ker By-product and Its Physicochemical Properties, Carbohydrates Polymers, Vol. 92, No. 1, 2013, pp. 289–296, http:/doi.org/10.1016/j.carbpol.2012.09.067. [7] T. M. H. Nguyen, H. L. Le, T. T. Ha, B. H. Bui, N. T. Le, V. H. Nguyen, T. V. A. Nguyen, Inhibitory Effect on Human Platelet Aggregation and Coagulation and Antioxidant Activity of Canna edulis Ker Gawl Rhizhomes and Its Secondary Metabolites, Journal of Ethnopharmacology, Vol. 263, 2020, pp. 113-136, https:/doi.org/10.1016/j.jep.2020.113136. [8] T. A. Y. Diaa, M. A. Ramada, A. A. Khalifa, Acetophenones, a Chalcone, a Chromone and Flavonoids from Pancratium Maritimum, Phytochemistry, Vol. 49, No. 8, pp. 1998, pp. 2579-2583, http:/doi.org/10.1016/S003109422(98)00429-4. [9] W. Koji, Y. Osanai, T. Imaizumi, S. Kanno, M. Takeshita, M. Ishikawa, Inhibitory Effect of The Alkyl Side Chain of Caffeic Acid Analogues on Lipopolysaccharide-induced Nitric Oxide Production in RAW264.7 Macrophages, Bioorganic Med. Chem., Vol. 16, No. 16, 2008, pp. 7795–7803, https:/doi.org/10.1016/j.bmc.2008.07.006. [10] C. Y. Wang, L. Han, K. Kang, C. L. Shao, Y. X. Wei, C. J. Zheng, H. S Guan, Secondary Metabolites From Green Algae Ulva Pertusa, Chemistry of Natural Compounds Vol. 46, No. 5, 2010, pp. 828-830. [11] C. T. Inh, N. T. H. Van, P. M. Quan, T. T. Q. Trang, T. A. Vien, N. T. Thuy, D. T. Thao, New Diterpenoid Isolated from Medicinal Plant Euphorbia tithymaloides (P.), Vietnam J. Chem., Vol. 54, 2016, pp. 274-279, https:/doi.org/10.15625/0866-7144.2016-00304 (in Vietnamese). [12] Q. Y. Li, H. Liang, B. Wang, Z. Z. Zhao, Chemical Constituents of Momordica charantia L, Yao Xue Xue Bao, Vol. 44, No. 9, 2009, pp. 1014-1018. [13] V. T. Diep, L. T. Loan, N. T. Thu, T. T. Ha, N. M. Khoi, N. H. Tuan, D. T. Ha, Triterpen, Flavonoid and Pyrimidine Compounds from The Aerial Parts of Dregea volubilis, Journal of Medicinal Materials, Vol. 24, No. 6, 2019, pp. 329-332. [14] H. M. Eid, D. Vallerand, A. Muhammad, T. Durst, P. S. Haddad, L. C. Martineau, Structural Constraints and the Importance of Lipophilicity for the Mitochondrial Uncoupling Activity of Naturally Occurring Caffeic Acid Esters with Potential for the Treatment of Insulin Resistance, Biochemical Pharmacology, Vol. 79, No. 3, 2010, pp. 444–454, https:/doi.org/10.1016/j.bcp.2009.08.026. [15] K. Takahashi, Y. Yoshioka, E. Kato, S. Katsuki, O. Iida, K. Hosokawa, J. Kawabata, Methyl Caffeate as a Glucosidase Inhibitor from Solanum Torvum fruits and the Activity of Related Compounds, Bioscience, Biotechnology and Biochemistry, Vol. 74, No. 4, 2010, pp. 741–745, https:/doi.org/10.1271/bbb.9087. [16] S. M. Fiuza, C. Gomes, L. J. Teixeira, M. T. G. D. Cruz, M. N. Cordeiro, N. Milhazes, F. Borges, M. P. Marques, Phenolic Acid Derivatives with Potential Anticancer Properties, a Structure-Activity Relationship Study Part 1: Methyl, Propyl and Octyl Esters of Caffeic and Gallic Acids, Bioorgan Med Chem, Vol. 12, No. 13, 2004, pp. 3581-3589, https:/doi.org/10.1016/j.bmc.2004.04.026. [17] S. P. Lee, G. Jun, E. Yoon, S. Park, C. Yang, Inhibitory Effect of Methyl Caffeate on Fos-Jun-DNA Complex Formation and Suppression of Cancer Cell Growth, Bulletin of Korean Chemical Society, Vol. 22, No. 10, 2001, pp. 1131-1135.